Resilience in aid workers in disaster and emergencies: a systematic review and thematic analysis - Sadeghi, Mahdi; Ghomian, Zohreh; Ebadi, Abbas; Rakhshanderou, Sakineh; Kolivand, Pirhossein (Frontiers in Psychology, 2025)
IntroductionResilience is a critical attribute for aid workers operating in disasters and emergencies, as it directly influences their ability to cope with high-stress environments’ psychological and physical challenges. Understanding the components of resilience can inform targeted interventions and training programs, ultimately fostering a more robust and adaptable workforce capable of meeting disaster response demands.ObjectivesThis study aimed to identify components of resilience in disaster and emergency aid workers by systematic review and thematic analysis.MethodologyThe systematic review adhered to the PRISMA protocol, searching various databases for resilience studies related to disaster aid workers from 1989 to November 2023. The study’s protocol is registered in PROSPERO under the registration number CRD42024508783. Articles were obtained from data resources such as Scopus, PubMed, Web of Science, and Google Scholar. At first, the keywords were determined based on the title and topic of the research, MeSH, previous texts, and the opinions of researchers and experts, and the search strategy was determined based on the keywords for each database. Inductive content analysis was used to identify components of resilience.ResultsFrom 3,198 searched studies, 17 were included in the final analysis. We identified five key components of resilience among disaster and emergency aid workers, which were categorized into two main groups: traits and process. Resilience traits include (1) health status, (2) essence and personality, (3) capability and competency, and resilience process includes (1) support platforms, and (2) organization and job.ConclusionThe study’s results can greatly help to understand the concept of resilience in disaster and emergency aid workers, which will ultimately serve as a guide for officials and researchers in planning and appropriate interventions to promote resilience in aid workers.Systematic review registrationThe study’s protocol is registered in PROSPERO under the registration number CRD42024508783. https://www.crd.york.ac.uk/PROSPERO/view/CRD42024508783.